Земельная политика и механизм управления земельными ресурсами в Эстонской Республике=Land Use Policy and Land Management in Estonia - Bogdanov Vladimir L. (Baltijskij Region, 2017)
This article studies the effect of land reform on the development of current land policy and land management efficiency. The authors present a review of materials focusing on the new land policy, land management and land use system at a new stage of Estonian development. This policy has led to the adoption of a new reform aimed at the municipalisation, privatisation, and denationalisation of real estate. The article describes mechanisms of the Romano-Germanic land management model, which has replaced the Soviet model in Estonia. It is shown that the model’s introduction has contributed to the development of the Republic’s land market and increased land use efficiency, in particular, in agriculture. There are positive trends towards land market development and an increase in production and investment in land use. Estonian land resources are a reliable strategic investment.